Morphological variant of pronator quadratus muscle : a case report - Ahmad Ruzain S,; Zar, Chi T; Syed Baharom Syed Ahmad Fuad, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Presented herein is a case of one different morphological anomaly of pronator quadratus (PQ) muscle. Here, the shape of PQ was not similar to the normal morphology of the muscle. The PQ muscle appeared to be in distinct triangular-shaped instead of quadrangular-shaped. In addition, this triangular-shaped was found in two sites i.e. proximal and distal. Significantly, the PQ muscle consisted of two fleshy red fibres and white aponeurosis. Proximally placed portion had a wide base and a narrower apex. The larger base was attached to the ulna and formed of fleshy red fibres which converged laterally to be continuous with aponeurosis ending on the radius. In contrast, the distal triangular portion had the fleshy fibres attached to the radius and converged medially to be continuous with aponeurotic portions on the ulna. Each portion were referred as pronator triangularis proximalis and pronator triangularis distalis. These variations might affect atypically in cases of forearm pronation. Information of these variations is important in hand surgeries and provide an additional knowledge on the relationship between morphology of PQ muscle and the limitation or the strength in the action of it.